The Great Depression. Informal Citizenship Education in a Usurpatory Democracy - Kobylarek, Aleksander; Madej, Martyna (Journal of Education Culture and Society, 2023)
Many countries have had people in power who were mower-mad and hungry for money as their representatives. In the case of Poland, there is quiet acquiescence to unethical actions by the authorities for the sake of one's own benefits, and a commonly accepted aversion to politicians (Zalec, 2022). of all kinds, which may be linked to the country's history. Those in power have become usurpers who do not care about the rules, the constitution or EU law, nor are they afraid of any punishment. Those who oppose these precedents become enemies, murderers or are accused of spreading propaganda. The country is divided into two camps - those who support the current government and those who are against it. The consequences do not only affect individuals, they are sometimes extended to entire municipalities where the current ruling party has lost the election. Ignorance or lack of civic knowledge can cause some voters to ignore the fact/not realise that their passivity is nevertheless supporting the current government. Crucial to combating this phenomenon is reliable informal citizenship education, carried out in an ongoing, emotionally charged way, appealing to the positive sides of informed citizenship and not discouraging to politics. The value of democracy should be taught. People should become open to discussing democracy, and the media should also repeat such positive messages. It is also important to remember what has happened by now.